Utilizing Used Cooking Oil for Aromatherapy Candle Production in Green Industry Programs - Bagus Tri Sutrisno; Ina Magdalena; Sa'odah (Jurnal Elementaria Edukasia, 2026)
Used cooking oil is often discarded carelessly after use. The disposal of used cooking oil into the environment, especially into waterways and soil, can cause serious pollution and contribute to ecosystem disruption as well as human health problems. At SDN Semanan 12 Pagi, the “Tersenyum” Program (Terima Sedekah Minyak Jelantah Untuk Mereka) has been implemented in collaboration with Rumah Sosial Kutub. The Tersenyum Program is a community empowerment initiative in the environmental field in the form of a Used Cooking Oil Donation Movement. The purpose of this study is to provide a creative and educational solution by transforming used cooking oil waste into a useful product, namely aromatherapy candles. By integrating a Project-Based Learning approach, the researcher seeks to encourage students to learn actively, creatively, and applicatively. This study employs a qualitative descriptive method, aiming to describe in depth the process of utilizing used cooking oil as a raw material for making aromatherapy candles. Data collection techniques include technique triangulation and source triangulation through interviews, observations, and documentation, as well as interviews with three different informants.